Dengue Cerebellitis: A Case Report and Literature Review - Khoo, Ching Soong (Am J Case Rep, 2018)
Patient: Male, 60 Final Diagnosis: Dengue cerebellitis Symptoms: Dizziness • fever • headaches • vomiting Medication: — Clinical Procedure: Lumbar puncture Specialty: Neurology OBJECTIVE: Unusual clinical course BACKGROUND: Dengue-associated neurological manifestations have recently been on the rise. Cerebellar syndrome complicating dengue fever has rarely been reported in the literature. We present a case report of dengue-associated cerebellar syndrome and performed a literature review to draw attention to this rare neurological complication. CASE REPORT: A 60-year-old man presented with 4 days of fever, myalgia, arthralgia, headaches, and warning symptoms (persistent diarrhea and vomiting). He was admitted with serologically-confirmed dengue fever. He had been well until day 8 of illness, when he developed cerebellar signs and symptoms. The temporal relationship with the recent dengue fever suggested that he had dengue cerebellitis. He recovered well, with no neurological sequelae upon our clinic visit. CONCLUSIONS: Dengue cerebellitis is a rare but recognized manifestation, which should be considered in patients from endemic areas of dengue fever who develop cerebellar syndrome.